Ethical acceptability of using generic consent for secondary use of data and biological samples in medical research - Frunză, Ana; Sandu, Antonio (Acta Bioethica, 2017)
The research idea starts from the previous identification of certain elements of generic consent for research activities found in informed consent (IC) forms used in therapeutic activities in hospitals that have the right to conduct medical research on human subjects in Northeast Romania. The paper questions the ethical acceptability of secondary use of data and biological samples in medical research, in the context of obtaining generic therapeutic consent from patients. The objective of the research is to analyze the Romanian context of using the IC obtained in therapeutic purposes as a starting point for the research activity. We wish to argue that the practice of obtaining a generic consent - for using the data obtained and the biological samples collected in the therapeutic process for secondary analysis - raises serious ethical issues regarding the validity and effectiveness of the IC.